Visual methodologies : an introduction to researching with visual materials / Gillian Rose. - Rose, Gillian, 1962- (SAGE, 2023)
Have you found some exciting images that you want to explore but don't know how to start your research or what methods to choose? Do you have a question about an aspect of visual culture that you want to answer? Whatever level of experience you have, this classic text will provide you with the key skills you need to complete a visual methods research project, understand the rationale behind each step, and engage with the contexts and power relations that shape our interpretation of visual images.